Report from the Central European Congress of Modernization, held on 23–25.10.2024 in Rzeszów - Grata, Paweł; Kinal, Jarosław (Studia Historiae Oeconomicae, 2025)
The Central European Congress of Modernization, an interdisciplinary scientific event dedicated to broadly understood modernization processes in Central and Eastern Europe and beyond, took place in Rzeszów from October 23 to 25, 2024. The Congress was organized by the University of Rzeszów and gathered over 130 speakers from 23 countries. The program included lectures on history, media studies, education, sociology, political science, economics, and cultural studies.